2012
DOI: 10.1007/s12565-012-0153-y
|View full text |Cite
|
Sign up to set email alerts
|

The nerves to the plantaris muscle and a bipennate part of the soleus muscle

Abstract: We performed nerve fiber analysis of the nerve to the plantaris muscle in 10 cases. Macroscopically, the nerve to the plantaris muscle has a tendency to branch off from the tibial nerve itself independent of the nerves to the gastrocnemius and soleus muscles (the triceps surae muscle). After removing the epineurium of the tibial nerve, it was revealed that, in all 10 cases, the nerve to the plantaris muscle formed a common funicular trunk with the nerve to a bipennate part of the soleus. This trunk is akin to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…More interestingly, researchers focused on PM innervations in contrast to anatomists who showed that this relationship seems to be much more complicated and reconsideration may be needed [21]. The nerve trunks to the PM arose from the nerve group of the deep posterior crural muscles rather than from the nerve groups of the superficial crural muscles and thus PM may be derived from anlage of the deep posterior crural muscles [21]. That clearly indicates that the perception of PM has changed over decades and our paper reveals how much we still do not know and how much could be discovered in future research about the structure that may be involved in the remodeling process instead of devolution as it was previously thought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, researchers focused on PM innervations in contrast to anatomists who showed that this relationship seems to be much more complicated and reconsideration may be needed [21]. The nerve trunks to the PM arose from the nerve group of the deep posterior crural muscles rather than from the nerve groups of the superficial crural muscles and thus PM may be derived from anlage of the deep posterior crural muscles [21]. That clearly indicates that the perception of PM has changed over decades and our paper reveals how much we still do not know and how much could be discovered in future research about the structure that may be involved in the remodeling process instead of devolution as it was previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays PM is considered by anatomists and embryologists a derivative of a deeper portion of the lateral head of the gastrocnemius and is often called "gastrocnemius tertius", which represents the third head of gastrocnemius due to its origin, which is often connected to the lateral head of gastrocnemius [20]. More interestingly, researchers focused on PM innervations in contrast to anatomists who showed that this relationship seems to be much more complicated and reconsideration may be needed [21]. The nerve trunks to the PM arose from the nerve group of the deep posterior crural muscles rather than from the nerve groups of the superficial crural muscles and thus PM may be derived from anlage of the deep posterior crural muscles [21].…”
Section: Discussionmentioning
confidence: 99%
“…The separated muscle mass is then further subdivided to form individual muscles, and since there is specificity between the nerves and muscles [11], information about innervation is essential to establish the identity of the muscle. In fact, descriptions of anatomical muscle morphology based on this innervation have been accumulated in eutherians [12][13][14][15][16][17][18][19][20][21][22][23][24], and inter-species comparisons have been performed (e.g. Emura [25]).…”
Section: Introductionmentioning
confidence: 99%
“…Remained phylogenetical question is whether the derivation of the anterior and posterior parts of the human soleus is the same or not. Some reports suggested that the bipennate anterior and major posterior parts of the human soleus have distinct origins (Bardeen, 1906; Okamoto et al, 2013), others suggested that these two parts of the muscle derive from a single origin (Jager & Moll, 1951; Sekiya, 1991). When discussing the homology and developmental derivation of muscles among primates, an important criterion to consider is the comparison of innervation patterns (Arakawa et al, 2005; Emura et al, 2020; Homma & Sakai, 1991; Koizumi & Sakai, 1995; Kudoh & Sakai, 2007; Okamoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%